Economic modeling for the US of the cost-efficiency and associated expanded treatment access of conversion to biosimilar pegfilgrastim-bmez from reference pegfilgrastim. (2nd August 2020) - McBride, Ali; Wang, Weijia; Campbell, Kim; Balu, Sanjeev; MacDonald, Karen; Abraham, Ivo
Abstract: Aims: For this economic analysis, we aimed to model: (1) the cost-efficiency of prophylaxis with biosimilar pegfilgrastim-bmez for chemotherapy-induced (febrile) neutropenia (CIN/FN) compared to reference pegfilgrastim, and (2) the expanded access to CIN/FN prophylaxis and anti-neoplastic treatment that could be achieved with biosimilar cost-savings on a budget-neutral basis. Methods: In a hypothetical panel of 20, 000 cancer patients receiving CIN/FN prophylaxis and using the average sales price (ASP) for the second quarter of 2019 for reference pegfilgrastim, we: conducted an ex ante simulation from the payer perspective of the cost-savings of 10–100% conversion from reference to biosimilar pegfilgrastim-bmez using drug price discounting ranging from 10–35%; estimated the budget-neutral expanded access to biosimilar pegfilgrastim-bmez enabled by these cost-savings; and estimated the budget-neutral expanded access to anti-neoplastic treatment with pembrolizumab. The simulations were replicated using fourth quarter 2019 wholesale acquisition cost (WAC) for reference pegfilgrastim and biosimilar pegfilgrastim-bmez in a post facto analysis. Results: In ASP simulations, cost-savings of using pegfilgrastim-bmez over reference pegfilgrastim in a 20, 000 patient panel range from $1.3 M (at 15% price discount) to $3 M (35%) at 10% conversion rate and from $6.4 M to $14.9 M, respectively, at 50% conversion. These savings could provide prophylaxis with pegfilgrastim-bmez to an additional 352 (15% discount) to 1, 076 patients (35%) at 10% conversion or 1, 764–5, 384, respectively, at 50% conversion. Alternatively, savings could be reallocated for anti-neoplastic treatment with pembrolizumab to 3 (15% discount) to 9 (35%) patients at 10% conversion or 19–45, respectively, at 50% conversion. When utilizing WAC, cost-savings range from $4.6 M (10% conversion) to $23.1 M (50%) which could provide pegfilgrastim-bmez to an additional 1, 174 (10% conversion) to 5, 873 patients (50%). Conclusions: Prophylaxis with biosimilar pegfilgrastim-bmez increases the value of cancer care by generating significant cost-savings that could be reallocated to provide expanded access to CIN/FN prevention and anti-neoplastic therapy on a budget-neutral basis.